MENINGKATKAN KOMUNIKASI ASERTIF DALAM RELASI SOSIAL PADA REMAJA DI PANTI ASUHAN SOS CHILDREN’S VILLAGE SEMARANG - Adiwena, Bartolomeus Yofana; Priyanto, Pius Heru (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
Adolescence is a period when someone begins to build broader social relationships and make decisions independently. However, many cases of adolescent social relationships actually provide negative experiences that hinder their development and threaten their future. Adolescents who live in orphanage have greater vulnerability to trapped in unhealthy social relationships. Assertiveness is the quality of a person to believe in himself, being able to communicate his thoughts, feelings, and emotions without driven by fear of others. Assertiveness assistance to adolescents in orphanages is important because assertiveness is a complement to the values ​​and norms they receive in schools and orphanages. Without assertiveness, their knowledge of values and norms will not be effective. Assertiveness is a psychological construct that can be changed through a behavioral intervention program. With this assertiveness assistance program,we hope adolescents in orphanage could develop positive social relationships and reject negative invitations or pressures that make them trapped in unhealthy relationships, so that their future could be better.